ANALISIS PERUBAHAN SUHU LINGKUNGAN TERHADAP KENYAMANAN MASYARAKAT DI DESA SUMBER TENGAH - Ahmad Nor Hamidy; Sudarti Sudarti; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2021)
Recently, there have been frequent changes of temperature and weather that are unpredictable and very extreme, causing people to feel uncomfortable with them. Therefore, this study aims to analyze the optimal temperature for the comfort of the community in Sumber Tengah Village, Binakal District, Bondowoso Regency. Sumber Tengah Village is located in the western part of Bondowoso and there are still many rice fields and plantations so the temperature is not too hot. Even so, the erratic temperature changes in Sumber Tengah Village also need to be analyzed to find out at what temperature people feel comfortable doing activities. In this study, data collection was carried out in the form of environmental temperature from 5 am to 9 pm for five days to see what time the lowest temperature, highest temperature, and optimum temperature are comfortable for the community. The data obtained will be compared with existing literature for further analysis.